2004
DOI: 10.1007/s00330-004-2583-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of iodinated and gadolinium contrast media during pregnancy and lactation

Abstract: The use of iodinated or gadolinium-based contrast media in pregnant or lactating women often causes concerns in the radiology department because of the principle of not exposing a fetus or neonate to any drugs. Because of the uncertainty about the use of contrast media during pregnancy and lactation, the Contrast Media Safety Committee of the European Society of Urogenital Radiology decided to review the literature and draw up guidelines. An extensive literature search was carried out and summarized in a repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
180
0
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 512 publications
(211 citation statements)
references
References 54 publications
1
180
0
22
Order By: Relevance
“…30 Un diametro aortico inferiore a 4 cm presenta un rischio lieve di dissezione (1%). 55 Anche se non c'è sufficiente letteratura sull'argomento, la gravidanza dovrebbe essere evitata in pazienti con diametro aortico superiore a 45 mm. 15 Se un paziente presenta un diametro dell'aorta di 40-45 mm, il clinico dovrà valutare altri fattori di rischio per dissezione (una storia familiare di dissezione, una crescita rapida del diametro aortico) prima di fornir suggerimenti riguardo una possibile gravidanza.…”
Section: Sindrome DI Marfanunclassified
See 2 more Smart Citations
“…30 Un diametro aortico inferiore a 4 cm presenta un rischio lieve di dissezione (1%). 55 Anche se non c'è sufficiente letteratura sull'argomento, la gravidanza dovrebbe essere evitata in pazienti con diametro aortico superiore a 45 mm. 15 Se un paziente presenta un diametro dell'aorta di 40-45 mm, il clinico dovrà valutare altri fattori di rischio per dissezione (una storia familiare di dissezione, una crescita rapida del diametro aortico) prima di fornir suggerimenti riguardo una possibile gravidanza.…”
Section: Sindrome DI Marfanunclassified
“…E' necessaria l'abolizione del tabagismo. 55 Secondo le linee guida GINA 36 le donne asmatiche in gravidanza non devono assolutamente interrompere il trattamento dell'asma ed il medico deve scegliere la dose più bassa di farmaci in grado di ottenere un controllo ottimale dell'asma.…”
Section: Asma Bronchialeunclassified
See 1 more Smart Citation
“…Animal studies have revealed teratogenic eff ects, but only at markedly increased and repeated doses. However, no harmful eff ects have been reported in human foetuses to date [65,66]. Because the half-life of gadolinium in the foetus is not known, gadolinium should be used with extreme caution during pregnancy and only if the potential maternal benefi ts clearly outweigh the risks to the foetus [63,64].…”
Section: Magnetic Resonance Venographymentioning
confidence: 99%
“…Small amounts of iodinated contrast agents can cross the placenta and enter the foetal circulation and the amniotic fl uid, exposing the foetus to additional risks [66]. No eff ect on foetal thyroid function has ever been reported, but a theoretical risk of iodine-induced neonatal hypothyroidism remains [49,89,96,97].…”
Section: Iodinated Contrast Agentsmentioning
confidence: 99%